Public administration the interdisciplinary study of government - Raadschelders, J. C. N. (Oxford : Oxford University Press, 2011)
'Public Administration' develops a comprehensive understanding of the internal structure and functioning of government in all its complexity and its interaction with society and its citizens.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public administration -- History